An α-Bi2O3/BiOBr core–shell heterojunction with high photocatalytic activity. Issue 7 (30th January 2017) - Shan, Lianwei; Liu, Yuteng; Chen, Hongtao; Wu, Ze; Han, Zhidong
Abstract : We prepared α-Bi2 O3 /BiOBr core–shell heterojunction via a facile in situ chemical transformation method. The prepared α-Bi2 O3 /BiOBr photocatalyst is characteristic of porous and high specific surface area, and shows high photocatalytic activity. Abstract : We prepared an α-Bi2 O3 /BiOBr core–shell heterojunction via a facile in situ chemical transformation method. Ultrathin BiOBr nanosheets were observed and these were found to be evenly distributed on the surface of α-Bi2 O3 /BiOBr by SEM and TEM. The results revealed that the prepared α-Bi2 O3 /BiOBr photocatalysts were porous, and their specific surface areas were found to be raised on comparing with α-Bi2 O3 and BiOBr. In our experiments, the photocatalytic activity of α-Bi2 O3 was obviously enhanced when assembling with ultrathin BiOBr compared with α-Bi2 O3 /BiOBr and the individual phase. It is considered that the surface porous structure increases the specific surface areas, which improved the adsorption characteristics of α-Bi2 O3 /BiOBr. The suitable band alignment (between α-Bi2 O3 and BiOBr) and oxygen vacancy effect can be attributed to the increased photocatalytic activity under visible irradiation.